GREEN INVESTMENTS AS A MECHANISM OF GLOBAL SUSTAINABLE DEVELOPMENT - STOLIARCHUK Yaroslavа; ILNYTSKYY, Denys; RUDKOVSKYY, Sergii (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article deals with the theoretical and applied aspects of the processes of green investments as a mechanism of global sustainable development in conditions of significant aggravation of the environmental problem that impacts global economic progress. The paper reveals significant impact of the global environmental problem on the transformation of the forms of international competitive relations and the priorities of international economic policy. The scope, structure and key trends of green investment processes, as well as the factors that determine their dynamics in recent decades, are researched. In the context of green institutionalism considerable attention is paid to the issue of the modern institutional structure of green investments and the economic motivation of various types of financial intermediaries regarding their participation in green investment processes on global scale. Key trends in processes of green investment of global economic development are defined: 1) increase in the needs of governments and business sectors, institutional investors and households, in attracting sustainable capital to increase their level of competitiveness on national and global markets; 2) diversification of financial instruments as a result of the implementation of fundamental ecological transformations of national economies; 3) diversification of the institutional structure of the global financial market and appearance of new institutions; 4) deepening of geographical and instrumental asymmetries and gaps. The need to create a favourable environment of implementation of green investment projects is emphasized as it is attributed to the core of modern mechanism of achieving the UN Sustainable Development Goals. Further scientific inquiries should investigate the effectiveness of instruments of environmental diplomacy of states in their close connection with green investments and growth of competition for global environmental leadership, the right to apply environmental sanctions and the formation of global environmental standards in the sphere of production and international trade.